Computed tomography of Wilson disease. - Kvícala, V; Vymazal, J; Nevsimalová, S (American Journal of Neuroradiology, 1983)
Computed tomography (CT) was performed on 25 patients with Wilson disease (hepatolenticular degeneration). The diagnosis was confirmed biochemically. CT was normal in seven patients, five of whom presented clinically with the hepatic form of the disease. In 10 patients, CT abnormalities were graded as mild: there were atrophic changes around the basal ganglia and in the cortex and cerebellum. In eight patients, besides areas of atrophy there were low absorption areas subcortically in the frontal lobi and in the cerebellar hemispheres, as well as brainstem atrophy. Hypodense lesions in the lentiform nucleus and the area of the dentate nucleus were also noted, although mathematical analysis in terms of decrease of Hounsfield units failed to demonstrate significant differences from normal values.